The Common Ratio Effect in Choice, Pricing, and Happiness Tasks†. (16th May 2017) - Schneider, Mark; Shor, Mikhael
Abstract: The Allais common ratio effect is one of the most robust violations of rational decision making under risk. In this paper, we conduct a novel test of the common ratio effect in which we elicit preferences for the common ratio choice alternatives in choice, pricing, and happiness rating tasks. We find large shifts in preference patterns across tasks, both within and between subjects. In particular, we find that both the consistency and distribution of responses differ systematically across tasks, with modal choices replicating the Allais preference pattern, modal happiness ratings exhibiting consistent risk aversion, and modal prices maximizing expected value. We discuss the predictions of various cognitive explanations of the common ratio effect in the context of our experiment. We find that a dual process framework provides the most complete account of our results. Surprisingly, we also find that although the Allais pattern was the modal behavior in the choice task, none of the 158 respondents in our experiment exhibited the Allais pattern simultaneously in choice, happiness, and pricing tasks. Our results constitute a new paradox for the leading theories of choice under risk. Copyright © 2017 John Wiley & Sons, Ltd.